Achieving Equity in Graduation Rates and Other Indicators of Success for Indigenous Learners in Canada - Louie, Dustin William; Prince, Leona (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2023)
This research project was designed to attend to inequity for Indigenous students, communities, and knowledges in a northern British Columbian district. The aims of the article are to share the systemic and individual transformation for Indigenous learners and their families based on the strengths and barriers they perceive in the system. Presented here are the results of extensive engagement with students, parents or guardians, teachers, administrators, and Indigenous communities that have led to novel practical approaches to governance, policy, programmatic design, and practice in a mainstream school district, resulting in improved school experiences for Indigenous learners. Through this research we illuminate the voices of Indigenous students and show how they guided the pursuit of equity in a Canadian school district. We examined the unconscious colonial agenda to understand how it emerges visibly and invisibly in a given context (Louie, 2020), while simultaneously creating distinct responses emerging from the teachings of Indigenous stakeholders and rights holders. Internal and external pressures on school districts often result in urgent demands for transformation, or at minimum, the urgent shift in perception of transformation (Daigle, 2019), but real and sustaining change cannot be rushed, borrowed, or created in isolation from the rest of the system.